Spotlight on platelets: summary of BBTS combined special interest group autumn meeting, November 2015. Issue 1 (February 2016) - Murphy, M. F.; Gill, R.; Moss, R.; Raghavan, M.; Stanworth, S. J.; Rowley, M.; Wallis, J.
SUMMARY: This conference first addressed aspects of component quality, highlighting the role of pathogen inactivation, the role of PAS or plasma in prolonging platelet viability and acceptable storage deviations. A series of talks on the medical use of platelets covered the role of platelet transfusion in preventing intracranial haemorrhage, platelet prophylaxis in haematological patients and the new trial of the HLA Matchmaker programme to provide epitope‐matched platelets. The session on the surgical use of platelets considered the role of platelet transfusions in patients on anti‐platelet agents, major trauma and interventional procedures and also the scope for tests of platelet function to direct therapy. The conference concluded with a panel discussion highlighting key areas of general interest, including the clinical use of platelets and near patient platelet function tests.